Multiple identities and crime: A study of Antillean women and girls in the Netherlands - Althoff, Martina (European Journal of Criminology, 2013)
The concept of intersectionality refers to the constructionist approach, which considers gender, class and race as categories of social inequality that cannot be added together but that intersect and construct each other. Social categories construct the social identities that affect what motivates people and how they operate. The question is how multiple identities come together in the context of crime? The paper reports the findings of a qualitative study that explored the concept of intersectionality when analysing crime. The study analysed the court files of Antillean women and girls living in the Netherlands and tried to find an explanation for their crime patterns in their struggle with their identity.
Keywords: LGBTQIA2+; antilles; approches et analyses; criminologie; discipline; europe; femmes* immigrantes; genre; identités; identités LGBTQIA2+; intersectionnalité; inégalités; pays-bas; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences; étude qualitative

Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape–with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
https://clio.columbia.edu/catalog/8481765
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexuelles

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis